«THE ROLE OF CONSULTING IN DEVELOPMENT OF THE AUDIT SERVICES MARKET» - Салямон, Виталий; Салямон-Михеева, Екатерина (SWorldJournal, 2020)
Annotation. The article discusses the place and features of consulting in the audit. A variety of types of consulting services was studied and relevant services provided by audit companies were examined. The market of consulting services is analyzed, the